Factors Associated with the Development of Adrenal Insufficiency in Patients with Juvenile Idiopathic Arthritis Who Received Systemic Corticosteroids - Gizem Zengin Ersoy; Müferet Ergüven; Metin Yıldız (Galenos Yayinevi, 2023)
Aim:In juvenile idiopathic arthritis (JIA), systemic corticosteroids are reserved for cases with serious organ involvement, those with macrophage activation syndrome, and in the presence of high disease activity in oligoarticular and polyarticular JIA. However, systemic steroids may lead to serious side effects linked to adrenal insufficiency (AI). This study aimed to investigate factors related to AI in children with JIA who received systemic steroids.Materials and Methods:Twenty-five children with AI (serum cortisol <18 μg/dL 30 minutes after adrenocorticotropic hormon stimulation) and 25 children without AI were included in this study. The subjects' characteristics, type of JIA, arthritis location, laboratory measurements, and number of joints involved were recorded. The type of glucocorticoid administered, the treatment protocol, and the cumulative steroid dose were recorded. The primary endpoint was the difference in clinical characteristics, laboratory measurements and systemic corticosteroid dose in those children with or without AI.Results:The median cumulative steroid dose was significantly higher in those patients with AI compared to those without [2,500 (1,370-4,400) mg vs. 963 (650-2,500) mg, p=0.010]. Patients with oligoarticular JIA had a 6.7-fold lower risk of AI compared to those with other JIA types [odds ratio (OR): 0.149, 95% confidence interval (CI): 0.035-0.643, p=0.011]. Those patients with higher cumulative steroid doses (>1,000 mg) had a 7.5-fold higher risk of AI than those with lower doses (OR: 7,500, 95% CI: 1,634-34,416, p=0.010).Conclusion:Our findings show that non-oligoarticular JIA and high cumulative steroid doses are predictive for AI development in this patient subset; thus, systemic corticosteroids should be reserved for more aggressive JIA types and the cumulative dose should be limited to 1,000 mg.